Application of Verbal De-Escalation and Assertive Training on Anger Control in Schizophrenia Patients with Violent Behavior - Wulandari, Sri; Hidayati, Laili Nur; Sri Purwanti, Titik (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Violent behavior is a harmful action directed toward oneself or others, commonly observed in patients with schizophrenia, and requires structured behavioral management such as de-escalation and assertiveness training. Objective: This case study aims to evaluate the effectiveness of de-escalation and assertiveness training in improving anger control among schizophrenia patients exhibiting violent behavior. Methods: A case study was conducted over four days one day in the Intensive Ward and three days in the Maintenance Ward on a male paranoid schizophrenia patient (Mr. J) using psychiatric nursing care guidelines from Muhammadiyah University of Yogyakarta and the PANSS-EC (Positive and Negative Syndrome Scale Excited Component). The intervention incorporated the KSS (frequent but brief contact) and BHSP (building a helping and supportive relationship) approaches. Results: After four days of intervention, the patient demonstrated improved emotional regulation, reduced irritability, and increased ability to communicate assertively. The PANSS-EC score decreased from 22 to 18, indicating a clinically meaningful reduction in the severity of violent behavior symptoms. The patient also showed greater self-awareness and cooperation during therapy sessions, suggesting enhanced anger control and self-regulation. Conclusion: De-escalation and assertiveness training are effective nursing interventions for reducing violent behavior and improving anger management in schizophrenia patients.